Delayed Diagnosis of Traumatic Rupture of Anterior Papillary Muscle of Tricuspid Valve; Importance of Trans-Esophageal Echocardiogram in the Evaluation of Major Blunt Chest Trauma - Ryan Bylsma; Mustafa Baldawi; Bruce Toporoff; Matthew Shin; Meghan Cochran-Yu; Davinder Ramsingh; Purvi Parwani; David G. Rabkin (Journal of Trauma and Injury)
We present a case of delayed diagnosis of traumatic tricuspid valve rupture in a patient who was emergently brought to the operating room for repair of lacerations to the heart and liver without intraoperative transesophageal echocardiography (TEE). Initial postoperative transthoracic echocardiography (TTE) did not show structural pathology. One week later, TTE with better image quality showed severe tricuspid regurgitation. Subsequently, TEE clearly demonstrated rupture of the anterior papillary muscle and flail anterior tricuspid leaflet. The case description is followed by a brief discussion of the utility of TEE in the setting of blunt thoracic trauma.